Bio-oil production from dry sewage sludge by fast pyrolysis in an electrically-heated fluidized bed reactor - Renato O. Arazo; Divine Angela D. Genuino; Mark Daniel G. de Luna; Sergio C. Capareda (Sustainable Environment Research, 2017)
The optimization of bio-oil produced from sewage sludge using fast pyrolysis in a fluidized bed reactor was investigated. Effects of temperature, sludge particle size and vapor residence time on bio-oil properties, such as yield, high heating value (HHV) and moisture content were evaluated through experimental and statistical analyses. Characterization of the pyrolysis products (bio-oil and biogas) was also done. Optimum conditions produced a bio-oil product with an HHV that is nearly twice as much as lignocellulosic-derived bio-oil, and with properties comparable to heavy fuel oil. Contrary to generally acidic bio-oil, the sludge-derived bio-oil has almost neutral pH which could minimize the pipeline and engine corrosions. The Fourier Transform Infrared and gas-chromatography and mass spectrometry analyses of bio-oil showed a dominant presence of gasoline-like compounds. These results demonstrate that fast pyrolysis of sewage sludge from domestic wastewater treatment plant is a favorable technology to produce biofuels for various applications.